Penafsiran Ayat-Ayat Ibadah (Shalat, Puasa, Zakat, Haji, Ilmu, Pernikahan, Wasiat) - Kurnia Gustammy C; Aisyah .; Naila Astari; Vanni Aulia Putri; Nurajija Nasution; Jihan Nurul Aisha; Edi Hermanto (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study examines the interpretation of verses on worship in the Qur'an, including prayer, fasting, zakat, hajj, knowledge, marriage, and wills, using a thematic interpretation approach (tafsīr maudhu'ī). This study aims to understand the normative and contextual meaning of verses on worship and their relevance to the formation of spirituality and the social order of Muslims. This study uses a qualitative method with a library research approach. Library research was chosen because this study focuses on the interpretation of verses on worship in the Qur'an as explained in various scientific works and relevant Islamic literature. The research data sources consist of written data sources in the form of the Qur'an and literature such as journal articles, textbooks, and scientific works that discuss the interpretation of verses on worship. The results of the study indicate that worship in the Qur'an is not only ritual in dimension, but also has moral, social, and humanitarian implications. Prayer fosters spiritual discipline, fasting fosters piety and social empathy, zakat fosters economic justice, the hajj fosters moral awareness and unity among the people, knowledge forms the basis for perfect worship, marriage fosters social peace, and a will ensures post-mortem justice. Thus, the verses of worship form an integral system of worship that unites the vertical and horizontal dimensions of human life.